Transformasi Sistem Lembaga Pendidikan Islam di Patani-Thailand Selatan - Ruslan Rasid; Abdul Munip; Hilman Djafar (Program Studi Pendidikan Islam, 2019)
This study aims to analyze the organization of the Islamic education system which aims to analyze the Muslim community in Patani-Thailand. The research methodology used in this study is qualitative-descriptive. The results showed that the transformation of the Islamic education system in Patani started from: First, the mosque or surau system. In the early days of Islam, this mosque / surau system was a place for "Tok Pakai" /Students learn the basic sciences of religion from the "Tok Guru" /Teacher until now the development of the mosque or surau system has integrated the Malay school system with the aim of preserving the Malay culture. Second, the traditional cottage system. In general, it is almost the same as the Islamic boarding schools in the archipelago, nowadays it is almost rare to find traditional Islamic boarding schools. Through various rules and policies of the Thai government, the proximity of all traditional Islamic boarding schools to transform into modern Islamic boarding schools (private Islamic schools). Third, the madrasah system. Non-Pondok madrasah, such as those found in the archipelago, have participated in Islamic education institutions in Patani, but due to pressure from the Thai government, this madrasah system only lasted for three years. The existing madrasah system has been integrated with the modern Islamic boarding school system. Fourth, the Malay school system. It was born because of public awareness to continue to preserve Malay culture and language.